Rethinking Regional Television: Intercultural Challenge in the Face of Media Profusion - Guyot, Jacques (Javnost-The Public, 1998)
In the context of internationalisation of audio-visual media, standardisation of exchanges and contents is also accompanied by a re-strengthening of local cultures. The claims for cultural and linguistic idiosyncrasies are directly linked to the development of regional television. Like in many other European regions, in Brittany (France), all the prerequisites seem fulfilled to launch a channel dedicated to the promotion of Breton culture and language. However, many uncertainties weigh on such a project. The size of the regional market may, of course, be an obstacle to financial viability. But, above all, the notion of identity is quite problematic in the construction of a regional media space: does it constitute a sufficiently solid and homogeneous base - from a sociological, cultural and linguistic point of view - to construct original television programming models which reflect the variety of social realities and cultural constructions?